KETERAMPILAN MENULIS PUISI DENGAN TEKNIK BRAINWRITING PADA SISWA KELAS X MADRASAH ALIYAH MELALUI PENERAPAN CONTEXTUAL APPROACH - Agus Wahyudi Wahyudi; Juanda (Universitas Terbuka, 2023)
This study aims to describe the poetry writing skills of grade X students. MA Darul Hikmah Temon Sawoo Ponorogo by utilizing brainwriting techniques and contextual approaches. Research data collection was carried out by interviews, observations, and tests. The data analysis method of this study is comparative descriptive analysis. Triangulation of data collection methods is the data validity technique used. Accuracy of theme and meaning, style, diction, and rhyme. All four aspects of poetry writing showed improved results. The grade point average before the study was 68, meeting the minimum completeness requirement of 75. The average value in cycle I is 75. A total of 15 students or 56% have met the Minimum Completeness Criteria (KKM). However, it has not met the target of 75% of students or 19 students scoring above KKM, so the percentage does not meet the achievement indicators. The average score of writing student poetry increased to 84% in Cycle II. Eighty-four percent of the 26 students had achieved minimum mastery scores. It can be concluded that the goal of achieving a minimum completion score of 75% of students can be achieved. As a result, Class X students of MA Darul Hikmah Temon Sawoo Ponorogo can improve their poetry writing skills by utilizing brainwriting strategies and Contextual Approaches.